Skin and subcutaneous tissue infections - Weronika Biaduń; Jakub Buczkowski; Aleksandra Romanowska; Aleksandra Padkowska; Michał Borawski; Aleksandra Ciuła; Klaudia Arciszewska; Mateusz Dobosz; Kinga Rogowska; Jakub Maciej Pieniążek (Journal of Education, Health and Sport)
Necrotizing infections of the skin and subcutaneous tissues are life-threatening conditions characterized by rapid progression and high mortality. The most common types include Fournier’s gangrene, gas gangrene, necrotizing fasciitis, and necrotizing myositis. These infections are often polymicrobial and involve both Gram-positive and Gram-negative bacteria capable of producing potent toxins. Diagnosis is based on clinical presentation, laboratory tests (e.g., LRINEC score), imaging techniques (ultrasound, CT, MRI), and microbiological evaluation. Effective treatment requires prompt surgical intervention, broad-spectrum empiric antibiotic therapy, and supportive care. Early recognition and aggressive management are essential to improve patient outcomes and reduce the risk of death.